Role of Botanical Gardens in Conservation of Rare Plants: A Case Study of Lead Botanic Garden of Shivaji University - Deshpande, Swapnaja Mukund; Yadav, Shrirang Ramchandra (Indian Forester, 2017)
Botanical gardens are the place of interest for local people as well as researchers. Most of the botanical gardens aim at conservation and education. They potentially offer community education about conservation, conservation attitudes, and encourage the public to support conservation efforts. Generally society is found to be less interested in conservation issues but the places like botanic gardens, museums, zoos, aquariums, heritage sites, natural areas and wildlife tourism sites can help to motivate the activities of public. Living collection of plant is most significant asset of botanical gardens. They seem to be most ideal places for conservation of RET, endemic and economically important plants of particular region. This paper addresses the need of enrolment of botanical gardens in conservation and environmental awareness among public. In this perspective Lead Botanic Garden (LBG) is wonderful concept nurtured by MoEF for conservation of RET species in the Post-CBD period under which the Botanical Garden of Shivaji University, Kolhapur (SUK) is recognized by MoEF as Lead Botanic Garden for Western India.